Creative Mathematical Thinking Ability Viewed from the Student Learning Styles in Treffinger Model (Universitas Negeri Semarang, 2019)
This study aims to determine the effectiveness of Treffinger Model in achieving the student’s creative mathematical thinking ability and their ability viewed from the students' learning styles. The type of study used was a mixed-method design of sequential explanatory. The first stage was quantitative data collection, and it was done using questionnaires to categorized the subject and tests. The next stage was qualitative data collection, and it was done using triangulation techniques such as questionnaires, tests, and interviews. The study population was the grade V Public Elementary School Gondangrejo, Magelang. Samples were grade VA as an experimental class with 20 students, and grade VB as the control class with 20 students. The results of this study indicated that Treffinger learning model effectively improved the ability of creative thinking viewed from the students' learning styles, this is indicated by the mathematical creative thinking ability of the experimental class students reaches the minimal past score, the mathematical creative thinking ability of the experimental class students is better than the control class, the creative thinking ability of students of divergent learning styles and convergent learning styles are at the 4th level or very creative and students' creative thinking abilities assimilation and accommodation learning styles are at 3th level or creative.